Non-Pharmacological Interventions To Reduce Back Pain in Pregnant Women: A Literature Review - Ema Arum Rukmasari; Gisa Agustin; Karisha Citra Elfani; Nur Rini Rahmawati; Diq Diq Ibrahim Siddiq Soebekti (GoAcademica Research & Publishing, 2023)
Back pain is pain that occurs in the lumbosacral area. The phenomenon of back pain experienced by pregnant women is one of the most frequently reported complaints. The purpose of this study was to find out what are the non-pharmacological interventions to reduce back pain in pregnant women. This study is a literature review to study non-pharmacological interventions to reduce back pain in pregnant women. Sources for conducting this literature review included ScienceDirect search studies, Google scholar, Sage journal and PubMed. There are several interventions that can be done to reduce back pain in pregnant women non-pharmacologically, namely unsupervised water exercises, Ear Acupuncture, Topical Use of Rosa Damascena (Rose) Oil, Yoga, Endorphine Massage, Effleurage Techniques and Warm Compresses and Effleurage Massage and Breath Relaxation In. Non-pharmacological interventions have significant value in reducing back pain in pregnant women and are safe to use.